Educational Theory in the 21st Century Science, Technology, Society and Education - Alpaydın, Yusuf; Demirli, Cihad (Maarif Global Education Series, 2022)
This open access book reviews the effects of the twenty-first century scientific-technological and social developments on the educational theory. The first part handles the subject, focusing on technology and educational philosophy. In the second part, the implications of new human and social conceptions towards the education paradigms are examined. In the chapters of the last part of the book, more practical dimensions of education are discussed. Transforming school designs, school management, learning-teaching approaches and teacher competencies are discussed in the context of broader social, cultural and technological changes.